Isolated Subscapularis Tendon Tear in a Skeletally Immature Soccer Player - Avanzi, Paolo; Dei Giudici, Luca; Giovarruscio, Roberto; Gigante, Antonio; Zorzi, Claudio (Joints, 2018)
Subscapularis injury in adolescents, usually associated to an avulsion fracture of the lesser humeral tuberosity, accounts for less than 2% of all fractures of the proximal humerus. Isolated tears of the subscapularis tendon without a history of dislocation and associated avulsion fractures are an even rarer occurrence, and treatment is controversial. This article describes a rare case of a 12-year-old suffering from an isolated subscapularis tear and discusses its management. The patient was evaluated at presentation, and at 1 to 2.5 months after he underwent a cuff tear arthroscopic repair with a single “all suture” anchor loaded with two wires, active/passive range of motion (A/PROM), Constant–Murley score, and American Shoulder and Elbow Surgeons (ASES) score were noted. Patient reported an excellent outcome, recovered the whole ROM, was pain free, and returned to the previous level of activity. Isolated avulsion of the subscapularis tendon requires a high index of suspicion for a proper diagnosis as early treatment is required for a good recovery. Arthroscopy reserves more advantages in proper hands, restoring the previous levels of function and activity. An increase in attention for this condition is mandatory in a society where many adolescents are getting more and more active in high levels of sport activities.
Keywords: subscapularis; shoulder; arthroscopy; adolescent